2005
DOI: 10.1007/s00425-004-1452-x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis emb175 and other ppr knockout mutants reveal essential roles for pentatricopeptide repeat (PPR) proteins in plant embryogenesis

Abstract: Pentatricopeptide repeat proteins (PPRPs) constitute one of the largest superfamilies in plants, with more than 440 identified in the Arabidopsis thaliana (L.) Heynh genome. While some PPRPs are known to take part in organelle gene expression, little is known about the broader biological contexts of PPRP gene function. Here, using developmental-and reverse-genetic approaches, we demonstrate that a number of PPRPs are essential early in plant development. We have characterized the Arabidopsis embryo-defective17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 46 publications
5
110
1
Order By: Relevance
“…Several reports have shown that loss of function of the PPR gene in Arabidopsis often caused an embryo-lethal phenotype, although at relatively late stages of embryogenesis compared with grp23 (Tzafrir et al, 2004;Cushing et al, 2005). In addition, they also showed dramatic morphological defects, such as enlarged shoot apices and stunted cotyledons (Cushing et al, 2005). As we did not observe such defects in grp23 mutants as a result of its early embryo lethality, the role of GRP23 in meristematic cells remains to be addressed.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Several reports have shown that loss of function of the PPR gene in Arabidopsis often caused an embryo-lethal phenotype, although at relatively late stages of embryogenesis compared with grp23 (Tzafrir et al, 2004;Cushing et al, 2005). In addition, they also showed dramatic morphological defects, such as enlarged shoot apices and stunted cotyledons (Cushing et al, 2005). As we did not observe such defects in grp23 mutants as a result of its early embryo lethality, the role of GRP23 in meristematic cells remains to be addressed.…”
Section: Discussionmentioning
confidence: 57%
“…It is not clear whether this is an indirect or direct cause of the loss of function of GRP23. Several reports have shown that loss of function of the PPR gene in Arabidopsis often caused an embryo-lethal phenotype, although at relatively late stages of embryogenesis compared with grp23 (Tzafrir et al, 2004;Cushing et al, 2005). In addition, they also showed dramatic morphological defects, such as enlarged shoot apices and stunted cotyledons (Cushing et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations